Investigating Social Status of Singaporean English - Inharjanto, Anselmus (Jurnal Humanipreneur, 2023)
This research aims to investigate the social status of Singaporean English, within the framework of Singapore’s multilingual societies. The context of World Englishes, especially the model crafted by Kachru, underlined the dynamic evolution of the language. This descriptive qualitative study explores empirically and theoretically the topic based on the secondary sources. The involvement of a related-literature review from previous researchers and experts, written in some journal articles and scientific books, has been considered. The result of the study demonstrates that the indigenization’s process of Singaporean English is linked to the roles and functions of the language in multilingual, multiethnic and multicultural contexts. Next, the management of multilingualism is achieved by the recognition of ethnic and linguistic diversity. Lastly, Singapore has been successful in language policy which equates ethnic identity and political role with one of four official languages.